Mach–Zehnder interferometric magnetic field sensor based on a photonic crystal fiber and magnetic fluid - Ding, Xiang Zi; Yang, Hang Zhou; Qiao, Xueguang; Zhang, Pan; Tian, Oin; Rong, Qiangzhou; Nazal, Nurul Asha Mohd; Lim, Kok Sing; Ahmad, Harith (Optical Society of America, 2018)
A Mach–Zehnder interferometric magnetic field sensor based on a photonic crystal fiber (PCF) and magnetic fluid (MF) was designed and experimentally demonstrated. The sensing probe consists of a single-mode-(SM)multimode-PCF-SM fiber structure through arc fusion splicing. It was then laser engrave notched with the femtosecond laser so that the PCF cladding was selectively infilled MF. A well-defined interference pattern was obtained on account of the tunable refractive index of the MF infilled PCF cladding. The transmission spectra of the proposed sensor under different magnetic field intensities have been measured and theoretically analyzed. The results show that the sensitivity of the proposed sensor can reach −0.13 dB∕mT and 0.07334 nm/mT in the magnetic field intensity from 1 mT to 20 mT and 2 mT to 20 mT, respectively.